SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN UZBEKISTAN: DEVELOPMENT AND ACTIVITY ANALYSIS - Murodova Nadira Gullievna (Scholar Express Journal, 2022)
This article describes the formation of professional motivation among future educators-teachers. The article deals with the organization of research works for students of the Faculty of Preschool Education, provides recommendations for the development of improved mechanisms and manuals based on a methodological approach to the development of professional motivation of students of higher educational institutions in teaching activities and suggests an organizational structure for the development of professional qualities.
Keywords: educator; formation; motive; activity